Book reviews. Issue 4 (1st October 2014) - Watkinson, Anthony
Abstract : EASE Science Editors' Handbook, 2nd edn Pippa Smart, Herve Maisonneuve, Arjan Polderman Redruth, European Association of Science Editors, 2013, viii + 231pp. 978‐0‐905988‐11‐5 (pbk) £24.99 plus postagehttp://www.ease.org.uk/publications/science‐editors‐handbook (EASE members can download chapter by chapter free of charge but there is no e‐edition officially available).